MALARIA PARASITE DENSITY, HAEMATOLOGY AND NUTRITIONAL INDICATORS IN BREASTFEEDING CHILDREN 0-2 YEARS AT CHUKWUEMEKA ODUMEGWU OJUKWU UNIVERSITY TEACHING HOSPITAL AWKA: A CROSS-SECTIONAL STUDY - Okeke, Obiageli Anthonia; Odili, Prosper Onyinye; Ishar, Cornelius Orjighjigh; Udeh, Nwabundo Peace; Imakwu, Cyril Ali; Okeke, Chioma Janefrances; Oraneli, Uche Boniface; Ikeh, Mulumba Ifeanyi; Nnatuanya, Ifebunandu Okwudilichukwu; Obiakor, Ugochukwu Anthony; Ukanwa, Chika Clement (FUDMA JOURNAL OF SCIENCES, 2025)
Malaria remains a major health issue caused by infected Anopheles mosquito especially in tropical and subtropical regions. Knowledge of haematological profile of infected persons is key in accurate diagnosis and effective treatment. This survey investigated the malaria parasite density, haematology and nutritional indicators in breastfeeding children 0-2 years at Chukwuemeka Odumegwu Ojukwu University Teaching Hospital, Awka. This hospital-based cross-sectional study was conducted from June to August 2024. Venous Blood samples were collected from the patients and analysed using microscopy and Automated Haematology Analyzer. Height and weight were measured using meter rule and weighing balance. Information on their breastfeeding practices was obtained with the aid of a questionnaire. Of the 114 breastfeeding children sampled, only 32.5% (n=37) were exclusively given breast milk. Those who received breast milk and water were 15.8% (n=18) while those who received breast milk and other food were 51.8% (n=59). Results from the survey showed that 26.3% of the breastfeeding children were positive for malaria. Male children had a higher mean parasite density than their female counterparts but the difference was insignificant (p>0.05). Parasite density across age groups increased as age increased, however, the variation in parasite density was not significantly different (p>0.05).  A significant negative correlation was found between the height of breastfeeding children and MCV (r=-0.39, p
Keywords: Breastfeeding; Children; Haematology; Malaria; Nutrition